Barriers to the Father-adolescent Sexual Communication: A Cross-sectional Study - Hadiseh Sadat Nabavi; Jila Ganji; Reza Ali Mohammadpour; Fatemeh Hamidi; Zohreh Shahhosseini (علوم بهداشتی ایران)
Background and Purpose: The majority of research on parent-adolescent sexual communication has predominantly focused on mothers, leaving fathers’ involvement in this matter largely unexplored. Therefore, this study seeks to identify the obstacles hindering sexual communication between fathers and adolescents. Materials and Methods: This cross-sectional study was performed on 196 fathers of adolescents aged 15 to 19 from August 2020 to January 2021 in northern Iran. A socio-demographic medical information form, a culturally validated parent-adolescent sexual communication barriers questionnaire, and the sexual communication topics between parents and adolescents were used to gather information. A logistic regression test was administered using SPSS software, version 18 to determine the barriers to sexual communication. Results: The mean age was 47.38±5.04 for fathers, 16.79±1.46 for boys, and 17.00±1.30 for girls. The prevalence of father-girl sexual communication (51.1%) was lower than that of father-boy sexual communication (55.8%). The most frequent barriers to fathers’ sexual communication with both genders were the adolescent’s embarrassment and the possibility of provoking their curiosity about sex. The logistic regressions showed that adolescents’ embarrassment and not trusting them and approving of them having sex were barriers to father-adolescent sexual communication (P<0.001). Conversely, adolescents asking more private questions were positive predictors of father-adolescent sexual conversation (P<0.001). Conclusion: The findings underscore the prevalence of adolescent embarrassment and concerns about sparking curiosity about sex as key obstacles to such communication. Additionally, the results highlight the importance of adolescents feeling trusted and supported by their fathers in discussing sexual topics. These insights emphasize the need for targeted interventions to address these barriers and promote healthier, more open communication between fathers and adolescents regarding sexual matters.